Pengaruh Minat Baca Terhadap Kemampuan Menulis Narasi Pada Siswa Kelas V SD Negeri 101874 Desa Tumpatan Nibung - ainun, Syarifah Ainun Harahap (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
This research aims to ; knowing the students' reading interest, knowing the students' narrative writing skills, knowing the effect of reading interest on the narrative writing skills of the fifth graders of SD Negeri 101874 Tumpatan Nibung. This research is a quantitative research. The population of this research is 17 students. Sampling using total random sampling. The variables studied were interest in reading and writing narratives. Data collection techniques using agket and tests. The validation test uses the Product Moment formula, while the reliability test uses the Alpha formula. Descriptive analysis by presenting data through tables, while parametric analysis through product moment correlation techniques. Based on the results of research and discussion, it can be concluded that, "1) students' reading interest is categorized as good, which is 47.1%, 2) students' writing skills are in good category, which is 35.3%, and 3) there is a positive and significant influence. between reading interest and narrative writing skills of fifth graders at SD Negeri 101874 Tumpatan Nibung Village. This is indicated by the value of rcount>rtable (0.555>0.227).